Opini Publik Pariwisata Pada Bromo sebagai Internation Union for Conservation of Nature Kategori II Taman Nasional - Riska Dwi Anggreani; Juariyah, Juariyah (MUKASI: Jurnal Ilmu Komunikasi, 2025)
This article examines public opinion on tourism in Bromo as an International Union for Conservation of Nature (IUCN) category II national park. Using qualitative methods that focus on understanding the phenomenon using non-numeric data such as text, images and audio to explain experiences related to the phenomenon. Qualitative research aims for researchers to be able to describe the phenomenon in detail and in depth such as the meaning behind the behavior that occurs, actions on phenomena and human experiences. The objectives to be achieved are to find out how public opinion is on tourism in Bromo and to find out the role of culinary in Bromo as an IUCN category II national park. Another objective is about how important the National Park is in supporting the IUCN mission in several ways, namely the national park provides several safe habitats for endangered plant and animal species, allowing their populations to recover and thrive. The results of activities and responses from tourists such as positive opinions, the division of categories in Bromo is very broad so that visitors will increase, such as including foreign tourists.